ANALYSIS OF SEDIMENTATION RATES AT THE MOUTH OF THE MESJID RIVER IN DUMAI CITY: IMPLICATIONS FOR SILTATION AND SEDIMENT TRANSPORT - Ilahi, Ilham; Mubarak, Mubarak; Ofirma, Farhat; Sari, Gita Purnama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The Mesjid River Estuary in Dumai City is an area prone to sediment accumulation due to the influence of river hydrology dynamics and interaction with oceanographic processes in coastal waters. The sedimentation phenomenon that occurs has a direct implication on the rate of estuary siltation and sediment transport patterns that affect the balance of the aquatic ecosystem. This study aims to analyze the sedimentation rate and sediment characteristics at the Mesjid River Estuary and examine the impact of sedimentation on siltation and sediment transport patterns. This study was conducted in December 2024 at the Mesjid River Estuary, Dumai City, with the aim of analyzing the sedimentation rate and its implications for siltation and sediment transport. Sedimentation in estuarine areas is an important phenomenon that affects changes in channel morphology, navigation capacity, and coastal ecosystem balance. Data collection was conducted at six research stations from upstream to downstream by recording water quality parameters, sediment characteristics, sedimentation rates, total suspended solids (TSS), and sediment transport. The results showed that the sedimentation rate ranged from 7.0 to 10.3 cm/year, with an average of 8.77 cm/year, which is relatively high compared to other estuaries in Southeast Asia. The average TSS value of 135 mg/l indicates a significant supply of sediment from land erosion and anthropogenic activities, while the sediment transport load reached 338.2 tons/year, confirming the role of the estuary as a center of material accumulation. These conditions accelerate siltation, limit the efficiency of maritime transportation, and alter coastal morphological dynamics, necessitating active management strategies and sustainable mitigation to maintain ecosystem functions and support the sustainability of local economic activities